The crisis of connection roots, consequences, and solutions - Way, Niobe 1963-; Ali, Alisha 1970-; Gilligan, Carol 1936-; Noguera, Pedro; Kirkland, David E. (New York New York University Press, 2018)
"The Crisis of Connection: Roots, Consequences, and Solutions" makes a compelling argument that one of the main problems of the 21st century is the crisis of connection both between and within individuals. The book provides evidence of the crisis and explores its causes and consequences. Eventually, "The Crisis of Connection" suggests possible solutions to the state of disconnection that the world has found itself in, encouraging the readers to pursue common humanity" --Provided by publisher.
Cartography of a lost time : mapping the crisis of connection / Carol Gilligan, Annie G. Rogers, and Normi Noel -- Boys' nature, boys' culture, and a crisis of connection / Judy Y. Chu -- Staying woke : raising black girls to resist disconnection / Janie Victoria Ward -- The "black box" : identity development and the crisis of connection among black adolescent boys / Leoandra Onnie Rogers -- In pursuit of our common humanity : the role of education in overcoming the empathy gap and the crisis of connection / Pedro Noguera -- Masculinity and our common humanity : "real" men vs "good" men / Michael Kimmel -- Slut shaming as a crisis of connection : fostering connections to fuel resistance / Deborah L. Tolman -- Humanizing the scientific method : the integration of structural competency and anti-oppression advocacy in addressing the crisis of connection through empirical research / Alisha Ali and Corianna Sichel -- Love pedagogy : teaching to disrupt / Lisa Arrastia -- Empathy as strategy for reconnecting to our common humanity / Mary Gordon -- The listening project : fostering connections in middle school classrooms / Niobe Way and Joseph Nelson -- The courage to care : building connection between young women and men with Shakespeare / Victoria Rhoades -- Splitting the world open : connection and disconnection among women teaching girls / Judith A. Dorney -- I want to learn from you : relational strategies to engage boys in school / Michael C. Reichert and Joseph D. Nelson -- "We don't come from the same background . . . but I get you" : performing our common humanity by creating original theater with girls / Dana Edell -- Letting men care : supporting engaged fatherhood to radically disrupt the gender binary / Gary Barker -- Re-humanization through communalized narrative for military veterans / Stephan Wolfert and Alisha Ali -- A new world : youth, voice, and connection / Khary Lazarre-White -- Resisting "us vs. them" : immigrants and our common humanity / Hirokazu Yoshikawa -- Love, actually : reflections from three religions / Rabbi Burton L. Visotzky, Reverend Chloe Breyer, and Dr. Hussein Rashid -- Afterword / David E. Kirkland.
Includes bibliographical references and index.
Keywords: Interpersonal relations -- Sociological aspects; Interpersonal relations -- Psychological aspects; Interpersonal relations -- Moral and ethical aspects